(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The government support and regulation instruments, aimed at developing the export potential of agrarian enterprises had been analyzed. The most effective ones were found. It was established that they are developed and adopted by the state documents and programs which were typically taken as a form of legislation, government regulations and decisions of regional or local authorities. It was found that the entire range of tools for state support of export potential of agrarian enterprises can be divided into financial and non-financial instruments groups. It was established that the financing instruments provided by public programs can be conducted by the state budget and off-budget sources. That is the principle of complex work initiation, creating conditions for stimulating. This principle allows allocating risks between the government and enterprises of the agrarian sector. The measures of governmental support should be final and enterprises which had received them should enter the mode of development based on respect of market principles.